Incentives in Academics: Why is There Tenure? - Carmichael, H. Lorne (Journal of Political Economy, 1988)
This paper models ancademic department as an internal labor market. The major problem facing the university administration is to ensure that members of its departments are willing to hire the best possible candidates. Academic tenure is seen to be a necessary condition for this. The analysis is also consistent with other aspects of the academic environment including "tenure-track" appointments, contract buy-outs, early retirement plans, and, when a budget crunch hits, the elimination of entire departments. The results extend in a simple way to other organizations in which members have an input into overall decisions.